Influência da luz e temperatura em cavidades e canais secretores em plântulas de Copaifera langsdorffii Desf. (Leguminosae-Caesalpinioideae): estudo anatômico e ultraestrutural - Buarque, Plácido Fabrício Silva Melo [UNESP] (2013)
Secretory spaces are distributed throughout the vegetative axis of Copaifera langsdorffii. They are constituted by uniseriate secretory epithelium and wide lumen, and represent a constitutive defense mechanism against herbivores and pathogens due to the produced secretion. In C. langsdorffii seedlings, oil cavities occur in the mesophyll of eophylls and in the cortex of epicotyl and hypocotyl, whereas oleoresin canals are present in the pith of epicotyl and hypocotyl. Evidences suggest that exogenous factors can influence the production of secretion in this species; however, nothing is known about these factors influencing the development of canals and cavities. This work aimed to investigate the influence of light and temperature on the density and lumen area of secretory canals and cavities in seedlings of C. langsdorffii, besides to study the influence of the temperature on the ultrastructural features of epithelial cells. Seedlings were maintained in climatic chamber under 2500lux, 1250lux and 250lux, and 15ºC, 25ºC and 35ºC. For quantitative anatomical analysis, samples of epicotyl and eophylls were processed according to usual techniques in plant anatomy. For ultrastructural studies, samples of eophylls were prepared following conventional techniques of transmission electron microscopy. Seedlings under 25ºC/1250lux presented higher density of cavities in eophylls and epicotyl, whereas seedlings under 25ºC/2500lux showed higher density of canals. This differential answer to light can be related to the distinctive origin of these secretory structures. Concerning the lumen area, variable answers were observed to cavities and canals. Ultrastructurally, epithelial cells of seedlings under 25ºC showed evidences of intense secretory activity. Alterations in mitochondria, plastids and endoplasmic reticulum were observed in seedlings under 15ºC and 35ºC. In seedlings under 35ºC, the epithelial cells showed evident signals of lysis, ...